Development of food pyramid application using Augmented Reality (AR) technology - Sakinatul Awatif Abdullah Waidi; Abu Bakar Ibrahim; Asma Hanee Ariffin; Mohd Sidek Fadhil Mohd Yunus; Nor Asiah Razak; Roznim Mohamad Rasli (Pejabat Karang Mengarang UPSI, 2021)
This study aims to develop a food pyramid application by using Augmented Reality (AR) technology to be one of the effective branches of education for children to better understand the definition of the food pyramid and how to take balanced nutrition according to category level in the pyramid. The objective of the study was to develop a food pyramid application using Augmented Reality (AR) technology that is simple and easy to play by children, build an app. This is so because the description is through a picture in reality and can clearly be visualized to them. The methodology that has been used in this study is the ADDIE model which has five phases. The results of the analytical data obtained through the quantitative approach that has been used on 22 respondents consisting of children, parents and experts have shown positive feedback on the functionality and usefulness of this application. This has been evidenced through the results of the study which showed that the percentage of respondents strongly agreed that this developed application is suitable for use by children for learning purposes and the percentage is equivalent to 91.7 percent. The analytical data collected were displayed in the form of tables, bar graphs and pie charts. Ultimately, as a result of testing on the application, it has been shown that this application can work well for the purpose of learning about the food pyramid to children. But there are still some improvements that can be done in the future to make this application more perfect for everyone's use.